An Experimental and Numerical Study on Acoustic Emission in the Process of Rock Damage at Different Stress Paths. (9th August 2021) - Liang, Dongxu; Zhang, Nong; Rong, Haoyu
Abstract : The study of the damage process of rock under external loads is good guidance for geotechnical construction design. The differences in rock damage processes and damage modes under different stress paths are rarely reported. To explore the effects of stress paths on rock damage processes, uniaxial compression experiments under three stress paths were conducted. Numerical simulation is also used to simulate the rock acoustic emission (AE) and fracture process. The results of the study indicate that the maximum acoustic emission events are at the peak of stress, and fractures are mainly formed at this stage. The peak of AE energy occurs before the peak of AE events. The damage pattern and fragmentation size of the rock are related to the way the stresses are loaded. It is noticed that there is appearance of a quiet period of AE events prior to the production of significant cracks. Minor damage to the rock is accompanied by the generation of bright white spots in the specimen, which is due to the high tensile or shear stress in the units. When the stress in these units exceeds their strength, the units break down and tiny cracks appear. As the external load increased, the cracks developed and penetrated, and the specimen was damaged. Under cyclic loading and unloading, the number of AE events increased significantly compared with the controlled displacement and controlled stress loading methods, and the radius of the AE circle became larger and the energy also increased, which indicates a greater degree of destruction of the rock under cyclic loading and unloading. The results of the study are of reference significance for rock crack propagation and fracture mode influenced by stress conditions and provide some guidance for construction design under different working conditions.